1970
DOI: 10.1055/s-0038-1654225
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Factor 4 (PF4) Release during Human Platelet Aggregation in Diabetic Patients

Abstract: SummaryThe release of platelet factor 4 during platelet aggregation was investigated in diabetic patients. We observed an increased release of platelet factor 4 in diabetic patients.The authors suggest that the increased release of platelet factor 4 may play an essential role in pathogenesis of thromboembolic complications in diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1973
1973
1993
1993

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Fibrin monomer complexes have been found to be elevated in our young diabetics and the results suggest that these are related to elevation of betalipoprotein levels, possibly because fatty acids and lipids promote platelet aggregation (Hoak, Warner & Connor, 1967). Indeed it has recently been reported that platelet factor IV release from platelets is greater in diabetics (Chmielewski & Farbiszewski, 1970) no doubt because coating of platelets by betalipoprotein enhances their sensitivity to aggregating agents.…”
Section: Discussionmentioning
confidence: 63%
“…Fibrin monomer complexes have been found to be elevated in our young diabetics and the results suggest that these are related to elevation of betalipoprotein levels, possibly because fatty acids and lipids promote platelet aggregation (Hoak, Warner & Connor, 1967). Indeed it has recently been reported that platelet factor IV release from platelets is greater in diabetics (Chmielewski & Farbiszewski, 1970) no doubt because coating of platelets by betalipoprotein enhances their sensitivity to aggregating agents.…”
Section: Discussionmentioning
confidence: 63%
“…The aspects of platelet function found to be deranged include adhesion (24), in vitro aggregability (25) and sensitivity to antiaggregating agents (26), a-granule content discharge (27,28), and thromboxane production (29). Such an activation was initially considered secondary to the presence of micro-and macroangiopathic alterations and/or to a condition of hyperglycemia (30).…”
Section: Conclusion-mentioning
confidence: 99%
“…In creased plasma BTG levels in diabetic pa tients are reported by a number of authors [6][7][8][9], although no significant difference as to BTG levels in normal subjects and in dia betic patients with complications was shown to occur by Campbell et al [10].…”
Section: Introductionmentioning
confidence: 99%